Індивідуальна профілактика насильницьких злочинів проти працівників органів внутрішніх справ України - Гладкова, Є. О.; Gladkova, Ye. O.; ORCID: http://orcid.org/0000-0003-4621-1738; ResearcherID: I-7032-2016 (Науковий вісник Дніпропетровського державного університету внутрішніх справ. - 2013. - № 1. - С. 439-444, 2013)
Висвітлено проблеми індивідуальної профілактики насильницьких злочинів проти працівників органів внутрішніх справ.

The article deals with the problem of individual prevention of violent crimes against police officers. Every year the number of violent crimes against law enforcement officers is increasing. The trend of attacks on the life of law enforcement officers in connection with their official duties does not also decrease. Individual prevention is targeted to work with a specific person, prone to illegal behavior and with his/her immediate environment. Person’s position in life is the basis for use to him/her of special preventive measures when his/her views, motives, orientation manifested in antisocial behavior. Individual prevention of violent crimes against police officers is largely associated with such changes affect the persons from whom you can expect to commit such crimes and their social environment (eg., a small social group). According to many scientists, the object of this activity should be certain contingent of people that live in a defined territory, behavior and lifestyle which indicate the real possibility of committing crimes. Complex process of interaction predict individual criminal behavior and individual preventive effect on the example of the violent perpetrator may be represented as follows: identified in the analysis and synthesis of the personal property, the quality, the factors underlying the creation psyhogramme relevant offender - the original model of the optimal set of qualities necessary for probable committing certain crimes in certain circumstances. Recommendations for personal prevention of violent crimes against police officers should include: 1) a theoretical justification for the possibility of correction or elimination of social and psychological causes of crime and improving operational reliability of certain categories of persons; 2) proposals for the formulation of a decision to such effects, taking into account social and psychological qualities contingent; 3) the characteristics and peculiarities of the individual precautions: optimal conditions for implementation timeframes and methods of correction, self-incentives, guidelines for monitoring and evaluation of changes.

Освещены проблемы индивидуальной профилактики насильственных преступлений против сотрудников внутренних дел.
Individual prevention of violent crimes against police officers of Ukraine
Индивидуальная профилактика насильственных преступлений против работников органов внутренних дел Украины
Гладкова, Є. О. Індивідуальна профілактика насильницьких злочинів проти працівників органів внутрішніх справ України / Є.О. Гладкова // Науковий вісник Дніпропетровського державного університету внутрішніх справ. - 2013. - № 1. - С. 439-444.
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Internal Affairs Agencies; органы внутренних дел; індивідуальна профілактика; ризик; виконання службових обов’язків; працівники ОВС; сотрудники ОВД; индивидуальная профилактика; риск; выполнение служебных обязанностей; police officers; individual prevention; risk; execution of official duties